Enhanced Biofilm Disruption in Methicillin-Resistant Staphylococcus aureus Using Rifampin and Fluoroquinolone Combinations - Yu Ri Kang; Joo-Young Park; Doo Ryeon Chung; Minhee Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Kyong Ran Peck (Pathogens)
Staphylococcus aureus biofilms complicate the treatment of device-related infections. We hypothesized that combining rifampin with fluoroquinolones could eradicate biofilms even in antimicrobial-resistant S. aureus strains. We determined the synergistic interactions of these combinations in a biofilm model. Thirty methicillin-resistant S. aureus (MRSA) isolates with varying susceptibility profiles were evaluated. Minimum biofilm eradication concentrations (MBECs) were determined using the Calgary Biofilm Device, and the synergy was assessed using the fractional biofilm eradication concentration (FBEC) index. Scanning electron microscopy (SEM) was performed on one strain, and confocal laser scanning microscopy (CLSM) was conducted on four strains for visualizing and evaluating the biofilm viability. The MBEC90 for rifampin and levofloxacin were 512 mg/L and 256 mg/L, respectively, and exceeded 1024 mg/L for ciprofloxacin. Synergy was observed in 56.7% of strains for both the rifampin + ciprofloxacin and rifampin + levofloxacin combinations, with no difference between the combinations. A higher ciprofloxacin MBEC (≥16 mg/L) increased the likelihood of synergy with rifampin by 18-fold. SEM and CLSM analyses in a subset of strains confirmed the enhanced biofilm disruption with rifampin + ciprofloxacin compared to ciprofloxacin alone. Our findings suggest that rifampin combined with ciprofloxacin or levofloxacin may synergistically eradicate MRSA biofilms, offering a potential treatment option for device-related infections when alternatives are limited.